Internationalization of Higher Education: The Pros and Cons - Akinbod, Akintola Ismaila; Shuhumi, Said Rashid Ali Al; Muhammed-Lawal, Adam Adesina (School of Social Sciences, USM, 2017)
Globalization in the twenty first century has reshaped virtually all facets of human life, higher education inclusive. Higher institutions of learning respond to this new trend through internationalization. Thus, citadels of learning are integrating international dimensions such as internationalized curriculum, exchange programme, recruitment of international students’ as well as hiring of prestigious international scholars in order to improve the school programme and cope with the unfolding challenges. Higher institutions of learning are undoubtedly becoming global actors and invariably undergoing aggressive modification. The modification does not only involve the curriculum taught in the school but also the aims and objectives of schooling, system of assessment and grading as well as academic governance and leadership are being revised in order to meet up with the contemporary global challenges. However different views have emerged in relation to internationalization of higher education. It has been regarded by some as a curse rather than a blessing for institution of learning, neo-colonialism rather than possibility for national development while to some it is an opportunity for global cooperation, cultural integration and economic interdependence. Based on these divergent views, this paper looks at the pros and cons of internationalization of higher education and how it can be effectively handled.